Teaching How to Teach: Microteaching (A Way to Build up Teaching Skills) - Reddy, KR (Journal of Gandaki Medical College-Nepal, 2019)
Microteaching is one of the most recent innovations in teacher training program which is used as a professional developmental tool in pre-service or in-service teacher training programs. Microteaching helps teachers to better understand the processes of teaching and learning and provides the opportunity to learn teaching skills, to study their own teaching, and to study the teaching of others. Microteaching is an organized, scaled-down teacher training program where a trainee teacher plans a short lesson, teaches it to a reduced group of students (Three to ten) in a 5 to 20 minute lesson, and then reflects on their teaching afterwards. The lesson is video recorded for either individual or peer review. The trainee teacher’s micro-lesson is reviewed, discussed, analyzed, and evaluated to give a feedback. Based on this feedback, the trainee teacher re-teaches the micro-lesson, incorporating those points raised during the discussion and analysis. The main objective of this article is to address and emphasize that microteaching has the potential to improve the teachers’ pedagogic skills, competencies, self-confidence, beliefs, and attitudes with minimum available facilities and to provide students with valuable teaching experiences and make them aware of the benefits and relationships between theory and practice.